Family talk intervention in paediatric oncology: a pilot study protocol - Malin Lövgren; Ulrika Kreicbergs; Camilla Udo (BMJ Publishing Group, 2019)
Introduction There is evidence that families with a child diagnosed with cancer need psychosocial support throughout the illness trajectory. Unfortunately, there is little research into psychosocial interventions for such families, especially interventions where the entire family is involved. The aim of this pilot study is therefore to evaluate a psychosocial intervention, the family talk intervention (FTI), in paediatric oncology in terms of study feasibility and potential effects.Methods and analysis This pretest/post-test intervention pilot study is based on families with a child diagnosed with cancer. All families that include at least one child aged 6-19 years (ill child and/or sibling) at one of the six paediatric oncology centres in Sweden between September 2018 and September 2019 will be asked about participation. The intervention consists of six meetings with the family (part of the family or the entire family), led by two interventionists. The core elements in the intervention are to support the families in talking about the illness and related subjects, support the parents in understanding the needs of their children and how to support them and support the families in identifying their strengths and how to use them best. Mixed methods are used to evaluate the intervention (web-based questionnaires, interviews, field notes and observations). Self-reported data from all family members are collected at baseline, directly after the intervention and 6 months later. Study outcomes are family communication, knowledge about the illness, resilience, quality of life and grief.Ethics and dissemination The study has been approved by the Regional Ethical Review Board in Stockholm (Dnr 2018/250-31/2 and 2018/1852-32). Data are processed in coded form, accessible only to the research team and stored at Ersta Sköndal Bräcke University College in a secure server.Trial registration ClinicalTrials.gov Identifier NCT03650530, registered in August 2018.